Land‐use history and an invasive grass affect tallgrass prairie sedge community composition. Issue 2 (30th September 2014) - McGranahan, Devan Allen; Engle, David M.; Mulloy, John T.; Miller, James R.; Debinski, Diane M.; Fraser, Lauchlan
Abstract Questions How abundant and diverse are sedges in upland tallgrass prairie? Are sedge communities associated with historical land use, abundance of an invasive species or different fire and grazing management regimes? How do sedge communities compare between reconstructed and intact grassland? Location Grand River Grasslands; working tallgrass prairie in north‐central Missouri and south‐central Iowa (US). Methods From 2008 to 2010, we surveyed the sedge species richness and measured canopy cover (an estimate of abundance) on 13 tallgrass prairie tracts, and measured canopy cover of an invasive C3 grass, tall fescue (Schedonorus phoenix (Scop.) Holub). Flowering sedges were identified to species and associated with wetland indicator status (WIS) and coefficients of conservatism (CoC). We calculated mean WIS, CoC, species richness (observed and estimated) and diversity (1/Simpson's D) for each tract. We used linear mixed‐effect regression and multivariate ordination to describe patterns of sedge abundance and community composition in terms of land‐use history (previously severely grazed intact prairie; previously ungrazed intact prairie; and reconstructed prairie), tall fescue abundance and current management (patch burn‐grazed, burned‐and‐grazed burned only). Results On average, sedges constituted 20 ± 0.01% of total plant abundance. Sedge abundance increased over time and was higher on intact prairie than on reconstructions, but grazing history of intact prairie did not affect sedge abundance. We observed 21 species that averaged moderate wetland affinity (mean WIS = −2.1 ± 0.2) and moderate affinity for undisturbed habitat (mean CoC = 4.5 ± 0.2 and 5.0 ± 0.1) from Iowa and Missouri lists, respectively). Species richness, diversity and conservatism did not vary with land‐use history, current experimental management or tall fescue abundance, although all three variables were associated with patterns of sedge community composition. Conclusions Diverse and abundant sedge communities provide a substantial forage resource for early season grazing. Neither historical grazing nor current fire/grazing management affected sedge diversity or floristic integrity. These data suggest grazing and the degree of invasion do not necessarily degrade entire native plant communities – responses likely vary among plant groups – but land‐use legacies have a persistent effect on sedge community composition.